Strengthening Customer Satisfaction Based on Promotions and Workshop Services - Maulana, Lucky Hikmat; Maulana, Hendri; Hofifah, Siti (Moneter: Jurnal Keuangan dan Perbankan, 2024)
The era of globalization impacts marketing activities in the transportation sector, one of which is motorcycles. In the increasingly growing motorcycle business, of course, it needs to be balanced with user satisfaction. This study aims to determine user satisfaction influenced by promotional variables and the quality of motorcycle repair shop services. The design of this study is descriptive and verification, with an analysis unit of 89 consumers. The data collection procedure uses literature and field studies through interviews and distributing questionnaires that have been tested for validity and reliability. The data analysis method uses multiple linear regression analysis, correlation coefficient analysis, determination coefficient analysis, and significance tests simultaneously and partially. The study's results indicate that simultaneously and partially the promotional variables and the quality of motorcycle repair shop services have a significant and positive effect on user satisfaction. It is recommended to increase the frequency and intensity of communication, as well as improve the motorcycle service process to be more reliable.